Long‐term trajectories of non‐native vegetation on islands globally. (23rd March 2023) - Walentowitz, Anna; Lenzner, Bernd; Essl, Franz; Strandberg, Nichola; Castilla‐Beltrán, Alvaro; Fernández‐Palacios, José María; Björck, Svante; Connor, Simon; Haberle, Simon G.; Ljung, Karl; Prebble, Matiu; Wilmshurst, Janet M.; et al.
Abstract: Human‐mediated changes in island vegetation are, among others, largely caused by the introduction and establishment of non‐native species. However, data on past changes in non‐native plant species abundance that predate historical documentation and censuses are scarce. Islands are among the few places where we can track human arrival in natural systems allowing us to reveal changes in vegetation dynamics with the arrival of non‐native species. We matched fossil pollen data with botanical status information (native, non‐native), and quantified the timing, trajectories and magnitude of non‐native plant vegetational change on 29 islands over the past 5000 years. We recorded a proportional increase in pollen of non‐native plant taxa within the last 1000 years. Individual island trajectories are context‐dependent and linked to island settlement histories. Our data show that non‐native plant introductions have a longer and more dynamic history than is generally recognized, with critical implications for biodiversity baselines and invasion biology. Abstract : Trajectories of non‐native vegetation started to rise within the past 1000 years globally. These trajectories differ between islands and partly depend on individual human settlement histories.